Vulnerability of the Nile Delta coastal areas to inundation by sea level rise - Hassaan, M A; Abdrabo, Mohamed (Springer, 2012)
Sea level changes are typically caused by several natural phenomena, including ocean thermal expansion, glacial melt from Greenland and Antarctica. Global average sea level is expected to rise, through the twenty-first century, according to the IPCC projections by between 0.18 and 0.59 cm. Such a rise in sea level will significantly impact coastal area of the Nile Delta, consisting generally of lowland and is densely populated areas and accommodates significant proportion of Egypt’s economic activities and built-up areas. The Nile Delta has been examined in several previous studies, which worked under various hypothetical sea level rise (SLR) scenarios and provided different estimates of areas susceptible to inundation due to SLR. The paper intends, in this respect, to identify areas, as well as land use/land cover, susceptible to inundation by SLR based upon most recent scenarios of SLR, by the year 2100 using GIS. The results indicate that about 22.49, 42.18, and 49.22 % of the total area of coastal governorates of the Nile Delta would be susceptible to inundation under different scenarios of SLR. Also, it was found that 15.56 % of the total areas of the Nile Delta that would be vulnerable to inundation due to land subsidence only, even in the absence of any rise in sea level. Moreover, it was found that a considerable proportion of these areas (ranging between 32.32 and 53.66 %) are currently either wetland or undeveloped areas. Furthermore, natural and/or man-made structures, such as the banks of the International Coastal Highway, were found to provide unintended protection to some of these areas. This suggests that the inundation impact of SLR on the Nile Delta is less than previously reported.